Hak Istimewa Profesi dan Situasi Penanggulangan Kebutaan - Tjahjono D. Gondhowiardjo (Majalah Oftalmologi Indonesia, 2020)
The basic paradigm of our profession are “blindness rehabilitation” and “prevention of blindness” could be seen in this edition, which is surprisingly dominated by the un-favorite Neuro Ophthalmology sub-speciality. Those manuscripts clearly showed that supported by cutting edge internal and external diagnostic devices and multi diciplines approach we successfully could preventing blindness. On the other side, due to the fact that in the Neurology dicipline there is a similar sub-speciality, thus we should reaching a minimal competency in Neuro Ophthalmology at least at similar level to their general competency. In reverse is the relatively easy to be judge, the corneal blindness. However, visual rehabilitation could only be provide suppose that there is corneal donor availlability. There is a good news and bad news in the corneal tranplantation data reported in this edition; the good news is that we already been competent to do the sophisticated descemet endothelial automated keratoplasty, and sad to know that iatrogenic is a leading causes for corneal transplantation. These fact, indirectly referring to the weakness of our internal “quality control” and “quality assurance” process in professional knowledge, skill and attitude to achieve the state of “a safe surgeon”. These is a serious profession’ issue, especially to the fact that it’s already coined as a negative perception to our national professional competency and achievement in relation to the reimbursement of cataract surgery from the Indonesian Social Security Administrator for Health (BPJS); which in turn might have an impact to the national prevention of blindness activitis. The rapid and steep raisement of reimbursement fund for ophthalmolgy problems since 2014; especially in relation to phacoemulsification cataract surgery, pterygium and medical fraud are the proper packaging for negative perception which successfully have an impact to the holistic and positive aspect of our effort to the prevention of blindness activity ; which unfortunately still classified “low” by International Agency in Prevention of Blindness (IAPB)....